2020
DOI: 10.21203/rs.3.rs-15847/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-economic inequalities in the association between alcohol-use disorder and depressive disorder among Thai adults: a population-based study

Abstract: Background: Previous evidence indicates significant associations between depressive disorders and alcohol use disorder (AUD) and their strong links with social conditions. This study aims to investigate the association between major depressive episode (MDE) and AUD across various socio-economic groups.Methods: We analysed data from the 2014 Thai National Health Examination Survey containing a random sample of 13,177 adults aged >20 years from the general population. The Alcohol Use Disorder Identification T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A study in morocco on participants between 15 and 18 years found that 94% were hazardous alcohol users 18 . Majority of the participants in our study were married with an annual income of U$6000, similar to other findings in Thailand and Nepal where most of the responded with alcohol problem were of the married group 15,19,20 . Another study in USA found that 77% of the participants were married with an annual income of more than U$150,000 21 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A study in morocco on participants between 15 and 18 years found that 94% were hazardous alcohol users 18 . Majority of the participants in our study were married with an annual income of U$6000, similar to other findings in Thailand and Nepal where most of the responded with alcohol problem were of the married group 15,19,20 . Another study in USA found that 77% of the participants were married with an annual income of more than U$150,000 21 .…”
Section: Discussionsupporting
confidence: 90%
“…These results were contrary to the findings in Thailand where it was found that high education level influenced the consumption of alcohol, there were more harmful alcohol users with secondary and university education than those of the primary school levels 23 . A study showed that college persons had a 160 times more likely to consume alcohol, thus education level had influence on alcohol consumption 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Because cultural contexts and socioeconomic status affect the prevalence of mental disorders among the Thai population, 11 we believe suicide characters in the urbanized region are different from their rural counterparts. Serious mental disorders are typically more common in urban environments 12 .…”
Section: Introductionmentioning
confidence: 98%
“…Because self-poisoning is the leading cause of poison exposure in Thailand, 8 identifying the unique characteristics of patients is necessary to develop a tailor-made multidimensional approach and suicidal prevention program in specific areas. 9,10 Because cultural contexts and socioeconomic status affect the prevalence of mental disorders among the Thai population, 11 we believe suicide characters in the urbanized region are different from their rural counterparts. Serious mental disorders are typically more common in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Parental drinking is associated with shorter sleep duration, worse sleep e ciency, and more long wake episodes in offspring 19,20 . Poor parental mental health and low socioeconomic status (SES) are also both associated with offspring sleep problems [21][22][23][24][25][26][27] , and these three risk factors -mental health, low SES and problem drinking -often co-occur 28,29 . To date, most studies have focused on single parental risk factors.…”
Section: Introductionmentioning
confidence: 99%